Critical Evaluation of Biofilm Formation Among Food Borne Bacterial Pathogens Isolated from Grape Peel and Methods to Tackle Biofilm - Ramasamy, Suganthi; Srinath, Jagadeshwari Akalu (Asian Journal of Biological and Life Sciences, 2020)
Biofilm forming food borne pathogens are a serious threat to food products and food industries as they have the capacity to attach to the substratum or to each other and covered by an exopolysaccharide matrix. Spoilage and pathogenic bacteria may form biofilms which increases post-processing contamination and risk to public health. The present study comprised of isolating the biofilm producing food borne pathogens from the peel of grape. The antibiotic resistance test was carried out and the isolates showing multiple antibiotic resistances were taken for the further study. For the selected isolates, the biofilm forming assays like Tube test method, Modified Congo Red Agar (MCRA) method and Micro Titre Plate (MTP) method was carried out. All the isolates showed moderate biofilm activity. Based on the morphological, physiological tests and 16s rRNA sequencing, the isolates were identified as Kocuria kristinae, Staphylococcus haemolyticus, Burkholderia cenocepacia and Enterobacter cloacae. The sequences were deposited in NCBI, Genbank and the accession numbers were assigned as MK615917, MK615918, MK615919 and MK615920 respectively. Different natural preservatives such as vinegar, lemon, tamarind, citric acid, sodium azide, sodium bicarbonate and Nisin were used for the biofilm eradication. Nisin in the concentration greater than 6.25mg/ml is suitable to inhibit the biofilm formation in Staphylococcus haemolyticusand 0.0487mg/ml for the remaining isolates. Vinegar in 1:2 dilution, Lemon in 1:4 dilution, Citric acid in 31.25mg/ml and Sodium azide in 12.5mg/ml will be optimal for inhibition of all the isolates. Sodium bicarbonate in 250mg/ml is optimal for inhibition ofStaphylococcus haemolyticusandEnterobacter cloacae.
Keywords: Biofilm eradication; Biofilm formation; Food pathogen; food preservatives; Micro titre plate assay; Nisin